Nonverbal, rather than verbal, functioning may predict cognitive flexibility among persons with autism spectrum disorder: A preliminary study. (June 2017) - Campbell, Colin Andrew; Russo, Natalie; Landry, Oriane; Jankowska, Anna Maria; Stubbert, Emily; Jacques, Sophie; Burack, Jacob A.
Abstract: Background: Cognitive flexibility may not be as impaired in persons with autism spectrum disorder (ASD) as expected by the clinical criterion of repetitive and perseverative behaviors (APA, 2013) and by their verbal abilities. In typically developing (TD) children and other groups, the development of cognitive flexibility is tightly linked to verbal development. However, nonverbal abilities may better predict cognitive flexibility in children with ASD because of their unique pattern of cognitive strengths and weaknesses. Method: We examined the relative influences of chronological age (CA), performance mental age (PMA), and verbal mental age (VMA) on cognitive flexibility as measured by performance on the Flexible Item Selection Task (FIST) among a group of 27 individuals with ASD with a wide range of IQs. The Leiter-R and PPVT-III estimated PMA and VMA, respectively. Results: Partial correlations indicated that PMA, but not VMA, related to switching performance on the FIST. Conclusion: Findings highlight the potential unique role of nonverbal abilities as a contributing factor to the development of cognitive flexibility among individuals with ASD. Nonverbal abilities may better support the development of cognitive flexibility in this particular population perhaps because their limited verbal abilities cannot contribute effectively to other cognitive processes such as cognitive flexibility.